Triumph : the untold story of Jesse Owens and Hitler's Olympics - Schaap, Jeremy 1969- (Mariner Book, 2008)
In 1936, against a backdrop of swastikas flying and storm troopers looming, an African-American son of sharecroppers set three world records and won an unprecedented four gold medals, single-handedly crushing Hitler's myth of Aryan supremacy. The story of Jesse Owens at the 1936 Olympic Games is that of a high-profile athlete giving a performance that transcends sports--but it is also the intimate and complex tale of the courage of one remarkable man. From the start, American participation in the games was controversial--a boycott attempt was thwarted by the president of the American Olympic Committee. Owens was befriended by a German rival, who helped Owens win the gold medal at his own expense; two Jewish sprinters were, at the last moment, denied the chance to compete for the United States out of misguided politeness to the Nazi hosts; and a myth was born that Hitler himself had snubbed Owens.--From publisher description.